2021
DOI: 10.1111/idh.12548
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic scaling in COVID‐era dentistry: A quantitative assessment of aerosol spread during simulated and clinical ultrasonic scaling procedures

Abstract: Objective: Healthcare agencies recommend limited use of aerosol-generating procedures to mitigate disease (COVID-19) transmission. However, total dispersion patterns of aerosols, particularly respirable droplets, via dental ultrasonic units is unclear. The purpose of this study was to characterize and map total spatter, droplet and aerosol dispersion during ultrasonic scaling in simulated and clinical contexts.Methods: Ultrasonic scaling was performed on dental simulation units using methylene blue dye-stained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Of course, this result does not fully represent the clinical situation, but according to the research of Alexandra et al., in 2021. 19 The study stated that the size range for influenza A (80–120 nm) largely encompasses that of SARS-CoV-2(70–110 nm), suggesting that most droplets detected in their simulated and clinical situation were capable of transporting SARS-CoV-2. In the above article, 19 the simulated test is also used dyes (methylene blue dye) as a test method to see the size of the droplet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, this result does not fully represent the clinical situation, but according to the research of Alexandra et al., in 2021. 19 The study stated that the size range for influenza A (80–120 nm) largely encompasses that of SARS-CoV-2(70–110 nm), suggesting that most droplets detected in their simulated and clinical situation were capable of transporting SARS-CoV-2. In the above article, 19 the simulated test is also used dyes (methylene blue dye) as a test method to see the size of the droplet.…”
Section: Discussionmentioning
confidence: 99%
“… 19 The study stated that the size range for influenza A (80–120 nm) largely encompasses that of SARS-CoV-2(70–110 nm), suggesting that most droplets detected in their simulated and clinical situation were capable of transporting SARS-CoV-2. In the above article, 19 the simulated test is also used dyes (methylene blue dye) as a test method to see the size of the droplet. It was also mentioned that the droplets of ultrasonic scaling may contain pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Brushing the teeth and cleaning the tongue at least twice a day and oral rinsing with antiseptic solutions (like hydrogen peroxide 0.5-1.5%, cetylpyridinium chloride 0.1-1.5% or povidone iodine 0.23-1% [ 85 ], 1.5% hydrogen peroxide, mixture of cetylpyridinium chloride, and povidone iodine) all effectively reduce oral bacterial load [ 86 88 ]. Studies have shown that these products effectively inactivate SARS, MERS, and H1N1 in 1 minute [ 87 90 ]. Finally, oral hygiene should be well improved, especially in ICU and the patients over 70, if anyone seeks to reduce risk of aspiration pneumonia and COVID complications [ 66 ].…”
Section: The Significance Of Oral Hygiene In Covid-19mentioning
confidence: 99%
“…The droplets made after ultrasonic scaling are able to travel long distances. Therefore, as the sensitivity of SARS-CoV-2 dictates, any related surface must be very well disinfected in compliance with the usual protocol for surface disinfection and sterilization of devices [ 87 ].…”
Section: Protection Against Covid-19 Pandemic Using Periodontal Treatmentsmentioning
confidence: 99%
“…The spread of particles is well established in dental literature. Pierre-Bez et al (2021) reported that at 0 to 1.2 m from the patient’s head, there is an increase in mass concentrations of particles compared to 1.2 to 2.4 m, indicating that these larger particles can settle and contaminate surfaces adjacent to the emission source. The same study found a significantly higher mass concentration of PM 1 compared to all other studied PM fractions at these distances ( Pierre-Bez et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%